Οι Γκαγκαούζοι και η καταγωγή τους - Ιορδάνογλου Αναστάσιος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1984)
The Gagaouzi constitute an ethnic group, dispersed to-day in Bulgaria, Rumania, the Soviet Union and Greece. Concerning their historical origin a number of theories have been proposed. Some researchers believe that the Gagaouzi are of Turkish origin, others that they are Bulgars, who were forced to speak the Turkish language, some think that they are Seldjuck Turks, who were settled in the Dobrudja by Izzeddin Keykâvus. A small number of researchers support the view that the Gagaouzi can be identified with the Turcophone orthodox population of Asia Minor, na mely the Karamanlides. Historical evidence and many similarities between the Gagaouzi and the Karamanlides, could lead one to conclude that these two ethnic groups may have common origins.